Influence of Traditional Sporting Games on the Development of Creative Skills in Team Sports. The Case of Football - Oboeuf, Alexandre; Hanneton, Sylvain; Buffet, Joséphine; Fantoni, Corinne; Labiadh, Lazhar (Frontiers in Psychology, 2020)
The aim of this present study is to investigate the influence of three learning contexts on the development of motor creativity of young footballers (8–9 years old). In team sport, creativity is a fundamental issue because it allows players to adapt in an environment of high social uncertainty. To carry out this work, we suggest a method for assessing motor creativity into ecological situations based on the analysis of praxical communications. Creativity originates from an interaction between divergence and convergence. In our case, the number of communications (fluidity) and the diversity of updated communications (flexibility) are our divergence indicators. Convergence, understood as the ability to make good decisions, is assessed by two expert judges (R > 0.90). Sixty boys’ football players (M = 8.67; SD = 0.3) coming from three football clubs participated in this research. The study lasted 2 years. Each year, a team of 10 players from each club participated in the research twice a week for 32 weeks (8 months), these groups attended different training sessions: (a) the control group (n = 20) followed a classical learning; (b) the decoding group (n = 20) attended training focused on learning the praxemes of football; (c) the traditional sporting games group (n = 20) followed a training session that was jointly focused on praxemes and the practice of traditional sporting games. The motor creativity of players and groups was assessed both at the beginning and at the end of the year during football matches. Compared to the control group, in the post-test, the group with the highest fluidity is the decoding group (p < 0.001) and the one with the highest fluidity is the traditional sporting games group. The latter group is also the one with the best convergence (p < 0.001). The results showed that traditional games can help develop players’ creative abilities. This research invites us to investigate the complementarity between the different offered training.